Soft Tissue and Bone Defect Management in Total Sacrectomy for Primary Sacral Tumors: A Systematic Review With Expert Recommendations. (15th October 2016) - Reynolds, Jeremy J.; Khundkar, Roba; Boriani, Stefano; Williams, Richard; Rhines, Laurence D.; Kawahara, Norio; Wolinsky, Jean-Paul; Gokaslan, Ziya L.; Varga, Peter P.
Abstract : Supplemental Digital Content is available in the text Abstract : Study Design: Systematic review and expert consensus. Objective: To address the following two questions: (A) Is there a difference in outcomes after spino-pelvic reconstruction of total sacrectomy defects compared with no reconstruction? (B) What constitutes best surgical technique for soft tissue and bony reconstruction after total sacrectomy? Summary of Background Data: The management of the soft tissue and bony defect after total sacrectomy for primary sacral tumors remains a challenge due to the complex anatomical relationships and biomechanical requirements. The scarcity of evidence-based literature in this specialized field makes it difficult for the treating surgeon to make an informed choice. Methods: A systematic literature review was performed (1950–2015), followed by a meeting of an international expert panel. Medline, Embase, and CINAHL databases and Cochrane Libraries were searched. Using the GRADE guidelines, the panel of experts formulated recommendations based on the available evidence. Results: Three hundred fifty-three studies were identified. Of these, 17 studies were included and were case series. Seven were evaluated as high quality of evidence and nine were of low quality. There were a total of 116 participants. Three studies included patients (n = 24) with no spino-pelvic reconstruction. One study included patients (n = 3) with vascularized bone reconstruction. Twelve studies included patients (n = 80) with no soft tissue reconstruction, three studies described patients with a local flap (n = 20), and four studies with patients having regional flap reconstruction (n = 16). Patients with or without spino-pelvic reconstruction had similar outcomes with regards to walking; however, most patients in the nonreconstructed group had some ilio-lumbar ligamentous stability preserved. The wound dehiscence and return to theater rates were higher in patients with no soft tissue reconstruction. Conclusion: We recommend spino-pelvic reconstruction be undertaken with soft tissue reconstruction after total sacrectomy. Level of Evidence: N/A